Sensitivity of yeast to lithium chloride connects the activity of YTA6 and YPR096C to translation of structured mRNAs. - Maryam Hajikarimlou; Houman Moteshareie; Katayoun Omidi; Mohsen Hooshyar; Sarah Shaikho; Tom Kazmirchuk; Daniel Burnside; Sarah Takallou; Narges Zare; Sasi Kumar Jagadeesan; Nathalie Puchacz; Mohan Babu; et al. (PLoS ONE)
Lithium Chloride (LiCl) toxicity, mode of action and cellular responses have been the subject of active investigations over the past decades. In yeast, LiCl treatment is reported to reduce the activity and alters the expression of PGM2, a gene that encodes a phosphoglucomutase involved in sugar metabolism. Reduced activity of phosphoglucomutase in the presence of galactose causes an accumulation of intermediate metabolites of galactose metabolism leading to a number of phenotypes including growth defect. In the current study, we identify two understudied yeast genes, YTA6 and YPR096C that when deleted, cell sensitivity to LiCl is increased when galactose is used as a carbon source. The 5'-UTR of PGM2 mRNA is structured. Using this region, we show that YTA6 and YPR096C influence the translation of PGM2 mRNA.